Non Surgical Extractfon of Residual Gallsitones - Tchekmedyan, Vartan; Belloso, Rogelio; Méndez, Hugo; Valls, Alberto; Romano, Dante (Cirugía del Uruguay, 1978)
The authors discuss the no·n surgical. extraction of residual gallstones. Records of 13 cases are presented, 9 having been successful. Of the 4 failures, only 1 is attributable to the method.